(3TaGA GdSbje HBjGJ GdNdjd EHQGgjes - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG GdMdHj ,J (B1032 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GJNP GHQGgje NdjdG hGLJHGg hGUWaGg s
(3BNQgG (B:s
(3eY Gf GdTghQ hGdCjGe EfeG JYO GdCjGe Ydi QCi CHj MfjaI dgG eJYI ef Pi GdMLI MQQ Pdc GHQGgje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B235 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1050s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs